Fermentation Process and Metabolic Flux of Ethanol Production from the Detoxified Hydrolyzate of Cassava Residue - Li, Xingjiang; Deng, Yongdong; Yang, Ying; Wei, Zhaojun; Cheng, Jieshun; Cao, Lili; Mu, Dongdong; Luo, Shuizhong; Zheng, Zhi; Jiang, Shaotong; Wu, Xuefeng (Frontiers in Microbiology, 2017)
With the growth of the world population, energy problems are becoming increasingly severe; therefore, sustainable energy sources have gained enormous importance. With respect to ethanol fuel production, biomass is gradually replacing grain as the main raw material. In this study, we explored the fermentation of five- and six-carbon sugars, the main biomass degradation products, into alcohol. We conducted mutagenic screening specifically for Candida tropicalis CICC1779 to obtain a strain that effectively used xylose (Candida tropicalis CICC1779-Dyd).By subsequently studying fermentation conditions under different initial liquid volume oxygen transfer coefficients (kLα), and coupling control of the aeration rate and agitation speed under optimal conditions, the optimal dissolved oxygen change curve was obtained. In addition, we constructed metabolic flow charts and equations to obtain a better understanding of the fermentation mechanism and to improve the ethanol yield. In our experiment, the ethanol production of the wild type stain was 17.58g•L-1 at a kLα of 120. The highest ethanol yield of the mutagenic strains was 24.85 g•L-1. The ethanol yield increased to 26.56 g•L-1 when the dissolved oxygen content was optimized, and the conversion of sugar into alcohol reached 0.447 g•g-1 glucose(the theoretical titer of yeast-metabolized xylose was 0.46 g ethanol/g xylose and the glucose ethanol fermentation titer was 0.51 g ethanol/g glucose).Finally, the detected activity of xylose reductase and xylose dehydrogenase was higher in the mutant strain than in the original, which indicated that the mutant strain（CICC1779-Dyd)could effectively utilize xylose for metabolism.